Determining the normal concentration of uranium in urine and application of the data to its biokinetics - Dang, H S; Pullat, V R; Pillai, K C (Health physics (1958), 1992)
A method was developed to determine the concentration of uranium (238U) in urine. This method involved preconcentration of uranium from urine with calcium phosphate neutron activation followed by simple radiochemical separation. Using this method, it was possible to detect 0.2 ng of 238U. The average and geometric mean concentration of uranium found in urine of subjects from a normal background environment was 12.8 and 9.4 ng L-1, respectively. The concentration of uranium in the urine and the daily intake of uranium by the same population was used to arrive at the gastrointestinal absorption factor (f1) for uranium incorporated in the diet. The f1 factor was estimated to be 1.6%.